Design Of Mobile-base Bali Regional Food Crops Recommendation Information System - suastika, i made; Kadyanan, I Gusti Agung Gede Arya (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 4 (2021): JELIKU Volume 9 No 4, Mei 2021, 2021)
Abstract Plant food is a necessary staple of each human being, in the process of cultivation is often the case things are not in want as failed harvests. These problems are caused by various factors such as weather that is not suitable for the needs of the plant or environmental conditions that are not suitable for its growth. Based on the problem that it takes a system of information that can provide information about the needs of that required by a plant food from the weather and environment of his life. The article will discuss the design of the application system of information on food crops to the area of Bali -based applications mobile. Keywords: Applications, Mobile, Information Systems, Food Crops, Weather, Environmental Conditions .